2011
DOI: 10.1111/j.1468-2389.2011.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness and Agreeableness as Moderators of the Relationship Between Neuroticism and Counterproductive Work Behaviors: A constructive replication

Abstract: Several previous studies examining the predictors of counterproductive work behaviors (CWBs) have found positive relationships for neuroticism and negative relationships for conscientiousness and agreeableness. We extend this research by examining whether employee personality traits interact with each other to influence CWBs. Because conscientiousness and agreeableness may suppress one's tendency to engage in CWBs, we hypothesized that the neuroticism-CWB relationship will be weaker among workers who are high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 47 publications
3
42
2
5
Order By: Relevance
“…Thereby, by means of these studies we could look at whether the theoretical linkages of our proposed model are supported or not. Another limitation concern, although the proposed model was not tested empirically in this study, it may be a guide for possible researches that according to past studies the measuring deviance by self-reported can be the best way (Bowling et al, 2011;Bowling & Eschleman, 2010). Additionally, in this study we did not consider any emotional or situational factors, which can be control variables (i.e.…”
Section: Resultsmentioning
confidence: 95%
“…Thereby, by means of these studies we could look at whether the theoretical linkages of our proposed model are supported or not. Another limitation concern, although the proposed model was not tested empirically in this study, it may be a guide for possible researches that according to past studies the measuring deviance by self-reported can be the best way (Bowling et al, 2011;Bowling & Eschleman, 2010). Additionally, in this study we did not consider any emotional or situational factors, which can be control variables (i.e.…”
Section: Resultsmentioning
confidence: 95%
“…Sobre o fator de segunda ordem, cabe reportar que, embora na versão original da WDS as autoras não tenham identificado esse fator geral, em estudos subsequentes (Babamiri et al, 2013;Bowling et al, 2011;Lee & Allen, 2002;O'Neill et al, 2011) o escore geral foi estimado tendo como argumento as altas correlações encontradas entre CCT-I e CCT-O. Esse dado aponta que a solução hierárquica possa ser a que melhor expressa a estrutura interna da escala, embora não tenham sido localizados estudos empíricos com essa mesma solução.…”
Section: Discussionunclassified
“…O índice de consistência interna para esse fator geral foi 0,85, sendo, portanto, satisfatório e semelhante ao reportado na literatura (Babamiri et al, 2013;Bowling et al, 2011;Lee & Allen, 2002;O'Neill et al, 2011). Já os índices para CCT-O e CCT-I foram baixos, o que pode se dever ao fato de tais dimensões ficarem representadas no presente estudo por um número menor de itens Os resultados da investigação sobre a evidência de validade convergente corroboraram as hipóteses formuladas.…”
Section: Discussionunclassified
See 2 more Smart Citations